Strategic sustainability reporting practices among industrial products and services companies: a comparative analysis before and during the pandemic crisis in Malaysia / Zuraidah Mohd Zam, Haslinda Yusoff and Rina Fadhilah Ismail - Mohd Zam, Zuraidah; Yusoff, Haslinda; Ismail, Rina Fadhilah (UiTM Cawangan Johor, 2025)
During the COVID-19 pandemic, non-essential businesses of Industrial Products and Services faced operational restrictions due to lockdowns imposed by the Malaysian Government. Economic disruptions erupted as the main effect of the lockdown, causing a reduction in their revenues. Consequently, the affected companies start to prioritise and focus on their short-term survival over sustainability activities that may be costly to them. However, they were obligated to report their sustainability initiatives and should make use of this occasion to share with stakeholders the strategy they have chosen to carry out sustainability initiatives' engagement in spite of the crisis. Thus, the purpose of this study is to examine strategic sustainability reporting practices disclosures before and during the COVID-19 pandemic crisis. This study used a modified multidimensional sustainability checklist to analyse the type of strategies, quality, and quantity of sustainability disclosures for 60 public listed Industrial Products and Services companies in Bursa Malaysia in 2018 and 2021. The disclosures of strategic sustainability reporting practices prior to and throughout the crisis were assessed using related statistical tests. The results showed that the companies' sustainability reporting disclosure changed significantly over the two studied years. Companies predominantly favoured the information strategy when performing sustainability initiatives. Notably, the quality and quantity of reporting in 2021 passed those in 2018. These results can be an indicator for stakeholders to ascertain whether a company's stance remains committed to sustainability initiatives for the long-term benefits or if its primary concern is ensuring its immediate business survival amidst the crisis.